Medical‐financial partnerships for improving financial and medical outcomes for lower‐income Americans: A systematic review - Julie Birkenmaier; Brandy R. Maynard; Harly M. Blumhagen; Hannah Shanks (Campbell Systematic Reviews)
Abstract Background Poverty is considered one of the social determinants of health (i.e., a range of social and environmental conditions that affect health and well‐being) because of its association with significant health problems. In recent years, healthcare settings have emerged as focal points for poverty interventions with direct health implications. Medical institutions are increasingly implementing financial partnerships to provide interventions targeted at improving the financial well‐being of patients with the dual objective of boosting appointment attendance rates and alleviating financial burdens on patients. While medical‐financial partnerships (MFPs) appear to be growing in popularity, it is unclear if these interventions positively impact financial and/or health outcomes. Objectives The purpose of this review is to inform policy and practice relevant to MFPs by analyzing and synthesizing empirical evidence related to their health and financial outcomes. The primary objectives of this review is to answer the following research questions: (1) What is the extent and quality of MFP intervention research? (2) What are the effects on financial outcomes of financial services embedded within healthcare settings? (3) What are the effects on health‐related outcomes of financial services embedded within healthcare settings? Search Methods We conducted a comprehensive search for published and gray literature from September to December 2023. We searched for and retrieved published studies from Google, Google Scholar, and 10 Electronic databases. We also searched five relevant websites and two trial registries for registered studies. We harvested from the reference lists of included studies and conducted forward citation searching using Google Scholar. Lastly, we contacted the first authors of the four included studies and requested information about unpublished studies, studies in progress, and published studies potentially missed in the other search activities. Selection Criteria Studies eligible for this review met the following criteria. First, studies must have used a prospective randomized controlled trial or quasi‐experimental (QED) research design with parallel cohorts. Second, studies must have involved an intervention that provides financial services on‐site within a healthcare setting. Third, the studies must have measured a financial outcome. Fourth, to meet the criteria for on‐site financial services, interventions must have included at least one of the following: (1) financial education, counseling or coaching, (2) credit counseling, or (3) the provision of services that assist patients to access financial products or services, such as free tax preparation services, or (4) services to increase income, such as screening for public benefits and assistance with the application process, as well as employment services (e.g., assistance with resume writing and job interviewing skills). Health‐related outcomes were extracted and analyzed, but were not required for eligibility. Data Collection and Analysis Searches were saved in the reference management software EndNote2, and duplicates were removed and uploaded to Rayyan. Four reviewers then completed title and abstract screening on 66,807 entries in Rayyan. Three reviewers independently reviewed the 26 articles that were moved forward for full‐text screening. A fourth reviewer reviewed discrepancies and made the final decision to include or exclude. Four studies that satisfied the inclusion criteria were retained for data extraction using a standardized extraction form. Because the included studies did not measure and report sufficient data to calculate effect sizes for similar outcomes, quantitative synthesis was not possible. Effect sizes were calculated when possible, and study outcomes were described. Main Results Of the four unique studies included in this review, two were randomized control trials and two were QEDs. Three of the four studies were conducted in pediatric settings. Two of the studies focused on tax preparation only as their financial intervention, both offering a VITA tax clinic on‐site in the healthcare clinic setting. One study featured financial coaching, which included a bundle of services such as one‐on‐one case management, budgeting and goal setting, and the fourth study provided financial counseling over two sessions delivered remotely. All four studies reported at least one financial outcome, and two studies reported at least one health‐related outcome. The evidence on the health and financial impacts of MFPs is limited due to the small number of included studies and lack of authors reporting data to calculate effect sizes. Results indicate small and nonsignificant effects of MFPs on financial outcomes reported, and some author‐reported positive statistically significant effects on attending appointments and adhering to vaccination schedules. The risk of bias assessment indicated important methodological weaknesses across included studies. Authors' Conclusions Although MFPs are becoming popular and have the potential to improve financial and health outcomes, there is an overall lack of evidence about whether MFPs are meeting their goals. Very few studies met inclusion criteria, and those that did were generally low quality, and therefore, we were unable to draw any conclusions regarding the intervention effects. Given the nascent nature of the research, the high level of enthusiasm for MFPS seems to be outpacing the evidence about their effectiveness on important outcomes. We advocate that healthcare settings invest first in rigorous research on pilot MFPs and disseminate their findings widely before making a determination about taking them to scale in practice and/or move ahead to integrate them into healthcare policy.